(untitled) (Journal of Naval Architecture and Marine Engineering, 2024)
This research paper explores the intricacies of heat and mass transfer in a vertical channel with immiscible fluids, delving into the dynamics of two-fluid flows. The study investigates the impact of variable viscosity and thermal conductivity on the transfer processes within the channel. Additionally, the incorporation of thermal slip effects is considered, adding a layer of complexity to the analysis. The Runge-Kutta sixth-order method, implemented through Mathematica ND Solve technics, ensuring accurate numerical simulations. An extensive examination of dimensionless velocity, angular momentum, energy, and diffusion is performed across all pertinent parameters, and the results are graphically illustrated to draw meaningful conclusions. This visual representation simplifies the comparison of transfer rates along the channel wall. Bar charts visually represent key elements of heat and mass transfer, including shear stress, the Sherwood number, and the Nusselt number, to make it easier to compare transfer rates along the channel wall. The outcome has shown that there is a significant effect of pertinent parameters on both heat and mass transfer. Journal of Naval Architecture and Marine Engineering, 21(2), 2024, P: 169- 182